The impact of retailers' loyalty programs in a supply chain context. (October 2022) - Bazargan, Amirhossein; Karray, Salma
Abstract: This paper studies the impact of retailers' loyalty programs (LPs) in a supply chain context. We consider a supply chain formed by one manufacturer selling its product through two competing retailers and focus on frequency loyalty programs that reward consumers with a free product after several purchases. Two different games are modeled: (1) a Stackelberg game, where the manufacturer is the leader and decides about the wholesale price, and the retailers are followers, and (2) a Nash game between the retailers, which decide about their price, whether to offer an LP and reward timing if they offer an LP. To do so, we formulate all players' demand/profit using a multinomial logit choice model where consumers' purchasing decisions depend on the utility they get from the different retailers' products and rewards. To include different consumer mentalities, we consider two parameters: sensitivity to reward value and sensitivity to time distance. Using an iterative algorithm, we numerically solve the games for the market's equilibrium prices and LP policies under serving consumers with different mentalities. We also study the market conditions under which retailers follow pre-set LP policies. Our main findings indicate that LPs can inflate prices at both levels of the supply chain, which can aggravate vertical externalities related to double marginalization. We show that supply chain managers should consider a profit-sharing agreement when retailers do not benefit from LPs. Further, we show that retailers should only offer LPs when consumers either have a low discount rate or/and they value rewards highly. Highlights: Profitability of loyalty programs (LP) in a supply chain with competing retailers. Game-theoretic model based on consumer choice. LP profitability depends on consumer valuation of time and rewards. LP can lead to vertical externalities related to double marginalization. Manufacturers can offer profit-sharing agreements.